Physical Activity Levels and Cognition in Women With Type 2 Diabetes - Devore, Elizabeth E. (Oxford University Press, 2009)
Persons with type 2 diabetes have a high risk of late-life cognitive impairment, and physical activity might be a potential target for modifying this risk. Therefore, the authors evaluated the association between physical activity level and cognition in women with type 2 diabetes. Beginning in 1995–2000, cognitive function was assessed in 1,550 Nurses’ Health Study participants aged ≥70 years with type 2 diabetes. Follow-up assessments were completed twice thereafter, at 2-year intervals. Multivariate-adjusted linear regression models were used to obtain mean differences in baseline cognitive scores and cognitive decline across tertiles of long-term physical activity. Initial results from age- and education-adjusted models indicated that greater physical activity levels were associated with better baseline cognition (for a global score averaging scores from 6 cognitive tests, P-trend = 0.02). However, results were substantially attenuated after adjustment for multiple potential confounders, largely because of physical disability indicators (global score: P-trend = 0.06); for example, the mean difference for the global score was 0.07 standard units (95% confidence interval: −0.01, 0.15) when comparing extreme tertiles. Results were similar for cognitive decline. These findings indicate little overall association between physical activity and cognition after adjustment for disability factors in older women with type 2 diabetes.